Carbon, nitrogen, and phosphorus storage in alpine grassland ecosystems of Tibet: effects of grazing exclusion. Issue 19 (23rd September 2015) - Lu, Xuyang; Yan, Yan; Sun, Jian; Zhang, Xiaoke; Chen, Youchao; Wang, Xiaodan; Cheng, Genwei
Abstract In recent decades, alpine grasslands have been seriously degraded on the Tibetan Plateau and grazing exclusion by fencing has been widely adopted to restore degraded grasslands since 2004. To elucidate how alpine grasslands carbon (C), nitrogen (N), and phosphorus (P) storage responds to this management strategy, three types of alpine grassland in nine counties in Tibet were selected to investigate C, N, and P storage in the environment by comparing free grazing (FG) and grazing exclusion (GE) treatments, which had run for 6–8 years. The results revealed that there were no significant differences in total ecosystem C, N, and P storage, as well as the C, N, and P stored in both total biomass and soil (0–30 cm) fractions between FG and GE grasslands. However, precipitation played a key role in controlling C, N, and P storage and distribution. With grazing exclusion, C and N stored in aboveground biomass significantly increased by 5.7 g m−2 and 0.1 g m−2, respectively, whereas the C and P stored in the soil surface layer (0–15 cm) significantly decreased by 862.9 g m−2 and 13.6 g m−2, respectively. Furthermore, the storage of the aboveground biomass C, N, and P was positively correlated with vegetation cover and negatively correlated with the biodiversity index, including Pielou evenness index, Shannon–Wiener diversity index, and Simpson dominance index. The storage of soil surface layer C, N, and P was positively correlated with soil silt content and negatively correlated with soil sand content. Our results demonstrated that grazing exclusion had no impact on total C, N, and P storage, as well as C, N, and P in both total biomass and soil (0–30 cm) fractions in the alpine grassland ecosystem. However, grazing exclusion could result in increased aboveground biomass C and N pools and decreased soil surface layer (0–15 cm) C and P pools.